Tranformasi Nilai Maja Labo Dahu dalam Penguatan Karakter Peserta Didik - Nurhaidah, Nurhaidah (Universitas Negeri Surabaya, 2024)
Transformation of the Maja Labo Dahu Value in Strengthening Student Character (Nurhaidah, 2024). The purpose of this research is to examine the transformation of the maja labo dahu value in strengthening the character of school members. This research uses a qualitative descriptive approach with data collection techniques through interviews, observation, documentation, and descriptive qualitative data analysis. The results of the study show that the transformation of the maja labo dahu value must be carried out collectively by all school components, namely the principal, teachers, education staff, and students as school members. These values are integrated into the curriculum in several ways. First, explore students' understanding of character strengthening programs in accordance with the Minister of Education and Culture Regulation No. 20 of 2018 concerning Strengthening Character Education in Formal Education Units, as well as students' understanding of the maja labo dahu value in daily life in the school environment. Second, transforming the maja labo dahu value which can be integrated into teaching and learning activities, incorporated into discussions on subjects, extracurricular activities, and teacher role models. Thus, the transformation of the maja labo dahu value can be carried out comprehensively and continuously through various aspects of the educational ecosystem in schools.